Optimalisasi teknik audit berbantuan komputer dalam pengawasan internal akuntabilitas keuangan desa - Riandewi W, Ni Luh; Sudana, I Putu; Rasmini, Ketut; Widanaputra, Anak Agung Gde Putu (Universitas Widya Mataram, 2025)
This research analyzes the factors that influence the successful adoption of Computer Assisted Audit Techniques (TABK), especially the Siswaskeudes Application. The topic of implementing the Siswaskeudes application by regional inspectorate internal auditors has never been researched before. This research aims to provide input regarding the implementation of Siswaskeudes to accommodate village financial supervision needs. This research is multi-locational, the theory used is UTAUT using qualitative descriptive analysis. The main research data is the results of interviews with 9 informants from 3 regional inspectorates. The results of the analysis show that the implementation of Siswaskeudes is influenced by the dimensions of performance expectancy, effort expectancy, social influence and facilitating conditions. The implementation of Siswaskeudes is still not optimal due to the absence of an independent Siswaskeudes implementation policy, the training duration is relatively short, and auditors' work patterns tend to be difficult to accept new innovations. The results of this research provide input for agencies to develop regulations for providing adequate infrastructure and training. Further research needs to be carried out at other regional inspectorates to obtain a more comprehensive analysis of Siswaskeudes implementation.